58. Dosimetric changes with Computed Tomography Automatic Tube Current Modulation techniques. (December 2018) - Spampinato, S.; Gueli, A.; Milone, P.; Raffaele, L.
Abstract : Purpose: The objective of the study is the verification of dose changes for a Computed Tomography (CT) Automatic Tube Current Modulation (ATCM) technique. In particular, the work aims to verify that (1) previsions of the CT scanner console (in terms of CTDIvol and DLP) are reflected in the dose distribution within the patient and (2) the experimental results coincide with the predictions of the noise theory on which the technique is based. For this purpose, an anthropomorphic Alderon RANDO (AR) phantom and Gafchromic® XR-QA2 films were used. Methods: Radiochromic films were cut to shape the AR phantom in two anatomical regions (shoulders and mid-chest). Since the ATCM algorithm used is based on the Noise Index (NI) parameter, three thorax exam protocols were chosen: reference (NI = 13), lower (NI = 10) and higher (NI = 16) noise. All other acquisition parameters during the three scans were maintained unchanged. CTDIvol and DLP values reported by the CT console were recorded after each exam to compare theoretical and experimental measurements. After dose calibration of the films, dose maps were normalized to the reference map (NI = 13) to obtain percentage variations. Experimental results were compared to the relative variations obtained from CT console and quantum noise theory. Results: The results showed that the information reported by the CT console in terms of CTDIvol and DLP variation are in agreement, on average, with experimental measurements. The dose distribution, however, is not uniform and CT console dose reports are purely indicative. Variations, in fact, are calculated by considering a uniform water phantom that does not represent the actual composition of the patient, as shown in Fig. 1. The values reported by the CT console are also in agreement with the prediction by the quantum noise theory. Conclusions: The study allowed to verify the dose information reported by the CT scanner console for an ATCM technique. The CTDIvol and DLP values represent, on average, the experimentally measured variation in the AR phantom. Although this evaluation represents an estimate, this method can be a starting point for further studies.